Motility Tracks: Technique for Quantitative Study of Bacterial Movement - Vaituzis, Z. (1969)
A method for recording movements of bacteria in time and space on a single photograph is described. Quantitative information on the behavior of various motile organisms may easily be obtained for comparative studies. The method possesses certain advantages over cinematography, and illustrations of applications of the technique are presented.